Bulk-Fill Direct Restorative Materials: An In Vitro Assessment of Their Physio-Mechanical Properties - Hui Woon Yeo; May Yeh Loo; Mariam Alkhabaz; Kai Chun Li; Joanne Jung Eun Choi; Abdullah Barazanchi (MDPI AG, 2021)
Bulk-fill restorative material has gained popularity in clinical practice, due to their perceived timesaving aspect. Objective was to compare the properties of bulk-fill direct restorative materials. Filtek Z350 (CR), Filtek One Bulk Fill Restorative (BF), Fuji IX and EQUIA Forte (EF) were compared. Thirty specimens from each material were prepared according to ISO 4049 for three-point flexural strength. Elastic moduli and hardness (n = 20) were evaluated using nanoindentation. Depth of cure (DC) (n = 20) was measured for BF at three different depths (2, 3, 4 mm) and at two irradiation times (20 and 40 s). Wear testing was carried out for three different periods (3, 6, 12 month(s)). All specimens were stored in 37 °C water for 24 h prior to testing. Results were evaluated using one-way ANOVA followed by a post hoc Bonferroni test (p < 0.05). BF and CR showed a significantly higher flexural strength than other groups (p < 0.05), and the highest Weibull modulus was found in CR. BF showed sufficient DC with at least 85%, at all thicknesses. CR and BF also had a high level of translucency than EF and Fuji IX. Significant differences in flexural strength were found among all materials except between Fuji IX and EF. While all material tested are suitable for use clinically, BF and CR have superior properties than GIC based bulk-fill.